Effect of age on children's pedestrian behaviour: Results from an observational study. (October 2018) - Wang, Huarong; Tan, Dingliang; Schwebel, David C.; Shi, Licheng; Miao, Lvqing
Highlights: Effect of age in pedestrian behaviours among pupils in grades one through six are studied by observing. Age effect was observed, with older children behaving more safely than younger ones. The older children violate more often in some basic pedestrian behaviour rules deliberately. The reason of risk-taking in the middle grades is perplexing and need further research. Children of different ages exhibit different characteristics of risky pedestrian behaviours. Abstract: Child pedestrians are disproportionately vulnerable to road traffic injuries, but it is unclear which aspects of pedestrian safety behaviours develop at what age. To create effective intervention programs, research on which pedestrian safety risks occur among which age group, is needed. This cross-sectional study was conducted to investigate the effect of age on pedestrian safety behaviours among 469 children in grades one through six (ages 6–14) from two primary schools in Nantong, China. The children were unobtrusively videotaped for 5 mornings whilst walking to school. Videotapes were then reviewed and coded for 10 pedestrian safety behaviours, including activities related to crossing streets (e.g. walking instead of running/hopping, observing traffic, using the crosswalk) and related to walking alongside busy streets (e.g. walking on sidewalk instead of running/hopping, walking without distraction). Results revealed that most children demonstrated safe behaviours in using the crosswalk (88.31%), walking instead of running/hopping while crossing the road (66.67%), and walking on the sidewalk instead of running or hopping (84.18%). Some unsafe behaviours were common, however, including ignoring traffic before crossing (84.85%) and while walking on the sidewalk (84.18%) and not waiting at the curb before crossing (60.17%). Age effects were observed, with older children behaving more safely than younger ones in most respects. For a few variables, however, such as walking outside the crosswalk lines, older children took more risks, perhaps deliberately because pedestrian safety skills were already fully developed and risky crossing efficiency was pursued. We also noted some risk-taking among children in the middle grades. For example, third-graders played most often when walking on sidewalks (19.23%). We conclude that children of different ages exhibit different characteristics of risky pedestrian behaviours and discuss implications for prevention.